Effect of Season on Blood Transfusion Patterns: A Retrospective Study - Felix Osei-Boakye; Nicholas Agyepong; Charles Nkansah; Abdul-Razak Saasi; Dorcas Serwaa; Mark Danquah; Kwesi Kattah; Mohammed Khadija; Fati Salifu; Andrea Owusu Antwi (Ital Publication, 2023)
Background: Different seasons present varied environmental factors that influence the occurrence of transfusion-driven diseases. Therefore, this study determined the patterns of blood transfusion among hospitalized patients and the effect of season on ABO/Rh phenotypes. Methods: A single-center retrospective cross-sectional study was conducted on 5089 hospitalized patients that were transfused with blood at Sunyani Municipal Hospital. Archived blood transfusion records were retrieved and analyzed using GraphPad Prism, and SPSS. The association, effect size, and yearly trends of transfusion patterns were determined. Results: The majority of the participants were females (63.0% [3208]), 36-49 years old (20.4% [1039]), O phenotype (48.1% [2447]), Rh-positive (93.1% [4737]), and transfused in the rainy season (61.0% [3103]). Patients' ABO was weakly associated with age (r = 0.07, p≤0.001) and season (r = 0.05, p = 0.008). Eighty percent (4053/5089) of the transfusions were ABO group-specific, and 28.3% (1146/4053) of this occurred at the emergency ward. The source of transfusion request was weakly associated with season (r = 0.1, p≤0.001) and type of transfusion (r = 0.1, p = 0.002). The rainy season (slope: 142.9, p≤0.001) and ABO-specific transfusions (slope: 219.5, p≤0.001) showed consistent increasing trends over the years. Conclusion: Blood transfusion was frequent among females, adults, Rh-positive and O phenotypes, and in the rainy season. Age and season were significantly associated with ABO, but not Rh. A transfusion request was associated with the season and type of transfusion, with the majority of transfusions occurring in the rainy season and emergency ward. There was an increasing yearly trend in blood transfusions.   Doi: 10.28991/SciMedJ-2023-05-02-03 Full Text: PDF